Palmyrena - city, hinterland and caravan trade between orient and occident : proceedings of the conference held in Athens, December 1-3, 2012 - Meyer, Jørgen Christian,; Seland, Eivind Heldaas,; Anfinset, Nils, (Archaeopress, 2016)
The contributions to this volume address the archaeology and history of the ancient Syrian city of Palmyra. Bringing together papers presented at a conference in Athens in December 2012 as a part of the a Syrian-Norwegian research project, it reflects international research and fieldwork that was going on until the outbreak of the Syrian civil war.